An improved medium for the anaerobic growth of Paracoccus denitrificans Pd1222 - Hahnke, Stefanie M.; Moosmann, Philipp; Erb, Tobias J.; Strous, Marc (Frontiers in Microbiology, 2014)
Paracoccus denitrificans is a well studied model organism with respect to its aerobic and anaerobic respiratory enzymes. However, until now, the growth medium for this organism has not been optimized for anaerobic growth. In particular, the requirements of P. denitrificans for trace elements (TEs) are not well known. In the present study we aimed to improve growth rates of P. denitrificans Pd1222 on a defined medium under anoxic conditions. We designed media containing different combinations of TEs at various concentrations, and tested their performance against previously reported media. Our results suggest that growth rate and yield depend on the availability and concentration of TEs in the medium. A chelated TE solution was more suitable than an acidified TE solution. Highest growth rates were achieved with medium comprising the TEs iron, manganese, molybdenum, copper and zinc ranging from 0.1 to 9 μM. On this medium, P. denitrificans Pd1222 grew with a generation time of 4.4 h under anoxic conditions and 2.8 h under oxic conditions. Diauxic growth was clearly shown with respect to nitrate and nitrite reduction under anoxic conditions.